Philosophy of Religious Nationalist Character Education in Islamic Boarding School-Based Vocational Schools - Nadri Taja; Mulyadi Al Fadhil; Riyandi Baehaqi; Revi Rusdatul Jannah (Jurnal Pendidikan Islam Indonesia, 2023)
This study aims to describe the philosophy of the religious nationalist character education program, as well as the role of schools in developing religious nationalist character e This study aims to describe the philosophy of the religious nationalist character education program, as well as the role of schools in developing religious nationalist character education for Dārut Tauhīd Vocational School students. The research method used is a case study. Data collection techniques in this study used observation, interviews, and documentation studies. The results of this study indicate that religious nationalist character education is implemented through basic leadership training activities, mataba (new santri ta'aruf period), Commemoration of National/Islamic Holidays, community service programs, student council elections, and cycles. The philosophical values of religious nationalist character education developed by Dārut Tauhīd Vocational School are sourced from the Koran, hadith, Daarut Tauhiid Culture, and the Merdeka Curriculum. Specifically, the religious nationalist character developed at Dārut Tauhid Vocational School is the BaKu character (Good and Strong). Keywords: character building; nationalist; religious ducation for Dārut Tauhīd Vocational School students. The research method used is a case study. Data collection techniques in this study used observation, interviews, and documentation studies. The results of this study indicate that religious nationalist character education is implemented through basic leadership training activities, mataba (new santri ta'aruf period), Commemoration of National/Islamic Holidays, community service programs, student council elections, and cycles. The philosophical values of religious nationalist character education developed by Dārut Tauhīd Vocational School are sourced from the Koran, hadith, Daarut Tauhiid Culture, and the Merdeka Curriculum. Specifically, the religious nationalist character developed at Dārut Tauhid Vocational School is the BaKu character (Good and Strong). Keywords: character building; nationalist; religious